Journalists imagining the European public sphere - Heikkilä, Heikki (Javnost (Ljubljana), 2006)
This article aims to analyse journalists' professional imagination in connection to EU news. A special attention is paid to the variety of ideas about European public sphere that inform (or fail to inform) journalists' work. The article is based on 149 semi-structured qualitative journalist interviews conducted in the home offices of mainstream news organisations in ten European countries. The article takes up Charles Taylor's idea that public sphere belongs to the key social imaginaries of modernity and treat journalists as important carriers of these social imaginaries. These professional imaginaries are traced by looking at how journalists perceive the locus of news, how they define their professional role vis-a-vis their audience, and finally, how they would describe the political and communication problems within the EU. From this reasoning three relatively coherent lines of thought were derived: classical professionalism, secular discourse, and cosmopolitan discourse. As a conclusion the article attempts to map out these different discourses in connection to modes of political communication. The three discourses detected in the article can be seen as contemporary versions of professionalism in European news organisations. As such, they do not give much ground to assume that a European public sphere would emerge out of national journalistic cultures. Given the emergent nature of publics and public spheres, this does not mean that such practices may not be developed outside journalism.
Keywords: European Union; Evropska unija; javnost; javna sfera; communication medium; mediji; journalism; novinarstvo; novinarji; odnosi z javnostmi; komuniciranje; communication